2002
DOI: 10.1093/heapro/17.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap: building the capacity of non-government organizations as advocates for health equity

Abstract: Seeking achievement of health equity has underpinned national government and global health policies for decades. However, major difficulties and challenges faced in the practice of achieving 'Health for All' has led to a recognition of the need to broaden the focus of efforts to improve health equity. Civil society groups have been identified as key stakeholders in attempts to achieve health equity, and the importance of strengthening their capacity to influence relevant government policy and practice has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 9 publications
0
40
0
1
Order By: Relevance
“…The other half (50.0%, n = 13) of the non-nursing research papers described action on SDOH, equity or public policy in general [22,23,[63][64][65][66][67][68][69][70][71][72][73]. Table 3 provides additional details for research papers by type of research, geographic location, and types of policy issues.…”
Section: Types Of Policy Issues Addressedmentioning
confidence: 99%
See 2 more Smart Citations
“…The other half (50.0%, n = 13) of the non-nursing research papers described action on SDOH, equity or public policy in general [22,23,[63][64][65][66][67][68][69][70][71][72][73]. Table 3 provides additional details for research papers by type of research, geographic location, and types of policy issues.…”
Section: Types Of Policy Issues Addressedmentioning
confidence: 99%
“…Policy advocacy was conceptualized as strategies taken to initiate, enact, and enforce structural and policy change(s) to benefit populations [24,61,63,71]. Policy advocacy approaches comprised a combination of independent and 'collective', 'intersectoral', or 'cross-sector' approaches to solving complex and multicasual public policy issues [23,24,55,78].…”
Section: Organizational Policy Advocacymentioning
confidence: 99%
See 1 more Smart Citation
“…(formal process of approaching policymakers), promotion or dissemination, and mobilizing public pressure. In their case study of 26 Australian NGOs, Nathan et al (2002) tried to understand how NGOs take action to influence government policy and practice for health equity. They found that NGOs had taken on the role of advocating for health equity.…”
Section: Civil Society Organizations' Engagement In the Policy Processmentioning
confidence: 99%
“…NVO įvardijamos kaip vieni reikšmingiausių sveikatos ugdymo srities partnerių, kurių veikla turi pridėtinę vertę visuomenės sveikatai [43,47], nors mokslo aplinkoje aptinkama nuomonių, kad reikėtų skirti didesnį dėmesį joms tinkamų mokymo modelių ir gebėjimų sveikatos priežiūros srityje stiprinimui [38]. Minimos organizacijos vis dažniau pasitelkiamos įgyvendinant tarptautinio ir nacionalinio lygmens įvairių sveikatos priežiūros ir ugdymo sričių projektus bei programas [15,18,39,55], atliekant sveikatos srities mokslinius tyrimus bei viešinant jų rezultatus [7,13,23], propaguojant fizinę [41], psichinę sveikatą [17,52], sveiką gyvenseną [1], vykdant lėtinių neinfekcinių ligų prevenciją [36,41], tenkinant specifinių grupių (pvz., moterų, vyresnio amžiaus asmenų, profesinių grupių, vietos bendruomenių), pacientų ir jų šeimų sveikatos ir socialinius poreikius [41].…”
Section: įVadasunclassified